2014
DOI: 10.1002/qj.2454
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic westward drift of Indian monsoon depressions

Abstract: A large fraction of the rain received by continental India is produced by cyclonic vortices with outer radii of about 1000 km that are contained within the larger scale South Asian monsoon flow. The more intense occurrences of these vortices are called monsoon depressions; these consist of bottom-heavy columns of relative vorticity that propagate to the northwest in time-mean low-level eastward flow. Previous studies have argued that this apparent upstream propagation is caused by dynamical lifting west of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
122
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(150 citation statements)
references
References 65 publications
10
122
3
Order By: Relevance
“…Observations show a dipole heating profile in the southwest quadrant of the monsoon depression vortex, which may contribute to the axial asymmetry of the vortex and its westward advection (Boos et al , 2016. One may imagine using the CQG modeling framework to examine what determines this structure by simulating a convective column in the southwest quarter forced by the advection associated with the monsoon depression vortex.…”
Section: Discussionmentioning
confidence: 97%
“…Observations show a dipole heating profile in the southwest quadrant of the monsoon depression vortex, which may contribute to the axial asymmetry of the vortex and its westward advection (Boos et al , 2016. One may imagine using the CQG modeling framework to examine what determines this structure by simulating a convective column in the southwest quarter forced by the advection associated with the monsoon depression vortex.…”
Section: Discussionmentioning
confidence: 97%
“…Boos et al () showed how IMD movement can be inferred through the advection of the 450 hPa PV maximum in the IMD by the local flow at that level, which is enhanced by beta drift, in which the PV anomalies induced by the meridional flow around the vortex generate a meridional northwestward advection of the vortex. Our arguments relating to the advection of the 850 hPa vortex maximum are probably complementary to the results of Boos et al (), in that we invoke the advection of the IMD structure, rather than wave‐propagation mechanisms presented by earlier authors. Boos et al () also show how the alignment of the 500 hPa PV structure with that at 700 hPa can explain the upwind advection of the MD PV at the lower level.…”
Section: Discussionmentioning
confidence: 99%
“…Hoskins and James, , p. 339). However, vorticity tendencies due to stretching remain significant (Boos et al ). Previous authors (Krishnamurti, ) have shown that baroclinic effects in monsoon depressions are in fact strong, and undoubtedly the effects of deep convection in the monsoon system introduce significant vorticity tendencies in the environment of a monsoon depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boos et al . [] have shown that these depressions are associated with potential vorticity columns that have a peak amplitude in the midtroposphere. They argue that horizontal, nonlinear adiabatic advection is responsible for their westward propagation.…”
Section: Introductionmentioning
confidence: 99%